ACTR-33. TUMOR TISSUE PENETRATION AND PHARMACODYNAMICS OF ONC201 IN ADULT RECURRENT GLIOBLASTOMA PATIENTS. (5th November 2018) - Arrillaga-Romany, Isabel; Odia, Yazmin; Allen, Joshua; Prabhu, Varun Vijay; Tarapore, Rohinton; Costa, Debora Vendramini; Shah, Neelima; Cukierman, Edna; Oster, Wolfgang; Mehta, Minesh; Wen, Patrick; Batchelor, Tracy
Abstract: BACKGROUND: ONC201 selectively antagonizes DRD2, crosses the blood-brain barrier and induces apoptosis in high grade gliomas and other advanced cancers. ONC201 efficacy is pronounced in glioma cells that harbor low DRD5 expression and is associated with induction of the ATF4/CHOP/DR5-mediated integrated stress response pathway. DRD2 antagonism also induces activation of NK and other immune cells. We previously reported the single agent activity of ONC201 in 17 adult patients with recurrent glioblastoma that demonstrated the safety, systemic pharmacodynamics, and a durable objective response when administered orally once every 3 weeks. Here, we evaluated the intratumoral drug concentrations and pharmacodynamic activity of ONC201 in adult recurrent glioblastoma patients that were treated on a weekly schedule. METHODS: Six patients >18 years old with first recurrence of glioblastoma who were eligible for salvage surgical resection were enrolled. ONC201 was administered orally as 625 mg once a week. Salvage surgery was performed approximately 24 hours after the second dose of ONC201 and patients continued on ONC201 until radiographic and/or clinical progression. Tumor tissue was flash-frozen and formalin-fixed for assessment of intratumoral drug concentrations by LC-MS and pharmacodynamics by IHC, respectively. RESULTS: Of the 6 enrolled patients, 5 had sufficient tissue for evaluation. Intratumoral drug concentrations exceeded therapeutic thresholds: median 1.5 µM (range 600 nM 9.3 µM). Investigation of biomarkers related to downstream signaling induced by ONC201 revealed heterogeneous intratumoral induction of ATF4/CHOP/DR5 expression and tumor cell apoptosis (TUNEL). Stronger induction of the pharmacodynamic signaling was associated with stronger induction of apoptosis and inversely associated with DRD5 expression, but not with drug concentration. No drug-related adverse events were reported in this cohort. Evaluation of immune cytokines and effectors molecules in serum and immune infiltration into the tumor is ongoing. CONCLUSIONS: ONC201 is biologically active and well tolerated in recurrent glioblastoma tumors when administered to adults.